The Impact of ERAS and Multidisciplinary Teams on Perioperative Management in Colorectal Cancer - Qianqian Zhang; Qinfeng Sun; Junfeng Li; Xing Fu; Yuhuan Wu; Jiawei Zhang; Xia Jin (Pain and Therapy)
Abstract Introduction The Enhanced Recovery After Surgery (ERAS) protocol, a comprehensive multimodal approach, aims to mitigate surgical stress, expedite recovery, and improve postoperative outcomes. Its implementation has notably advanced perioperative care in colorectal cancer surgeries. Integrating ERAS with multidisciplinary collaboration, involving surgery, anesthesia, nursing, and nutrition, may further enhance patient outcomes, making it a significant focus in clinical practice. Methods This study assessed the effectiveness of integrating the ERAS model with multidisciplinary collaboration during the perioperative period in colorectal cancer patients. A total of 117 patients scheduled for elective surgery at Haiyan People's Hospital between August 2023 and April 2024 were randomly assigned to either a control group (n = 59), receiving traditional care, or an experimental group (n = 58), receiving ERAS-based multidisciplinary care. Key outcomes related to postoperative rehabilitation were evaluated. Results Patients in the ERAS group demonstrated significantly shorter hospital stays, quicker catheter removal, and earlier mobilization compared to the control group (P < 0.0001 for all). Additionally, the ERAS group exhibited reduced postoperative inflammatory responses, as indicated by significantly lower interleukin-6 levels on the first postoperative day (P = 0.0247). The quality of life was significantly higher in the ERAS group (P < 0.05). Furthermore, the ERAS group incurred lower total hospitalization expenses than the control group (P = 0.0011). Conclusion These findings confirm the benefits of the ERAS protocol in enhancing postoperative recovery in colorectal cancer surgeries. The study highlights the importance of a multidisciplinary approach in optimizing patient outcomes and reducing the burden on hospital resources.